Diachronic and synchronic analysis of lexicographic processes of minority languages in Scotland: a contrastive approach - Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Lemeshchenko-Lahoda, Viktoriia (My University, 2021)
The paper offers a diachronic and synchronic analysis of the lexicographic processes of the minority languages in Scotland – Scottish Gaelic and Scots. For the first time, three periods (period of glossaries, historical period, modern “educational” period) of the Scottish Gaelic lexicography, and four periods (period of glossaries, pre-scientific period and dialectological period, historical period and scientific period) of еру Scots lexicography were outlined. The author discusses the diachronic and synchronic analysis of lexicographic sources, singles out common and divergent features of both lexicographic processes development, as well as the basic principles and approaches to compiling dictionaries. For the Scottish-Gaelic lexicography, it is absolutely untypical to compile dictionaries of dialectal words; to interpret the Gaelic language as a dialect of Irish, in contrast to the Scots, which for a long period of its development was perceived as a dialect of English, which prompted the lexicographers to compile dictionaries of dialectal vocabulary. A significant advantage of Scottish Gaelic dictionaries lies in the fact that English-Gaelic dictionaries appeared decades earlier in comparison with similar editions in the Scots language. Despite the fact that Scottish Gaelic is the official language of Scotland, Scottish Gaelic lexicography, compared to the Scots one, is significantly inferior both in the number of published dictionaries and in the quality of their content (macro- and microstructure). Both lexicographic processes are characterized by the lack of monolingual dictionaries. All publications are bilingual (translated into English, or from English, rarely in other languages).
Keywords: minority languages; Scottish Gaelic; Scots; lexicography; lexicographic process; diachronic analysis; synchronic analysis